How to cope with stress in special needs education? Stress-inducing dysfunctional cognitions of teacher students: the perspective of professionalisation. Issue 2 (2nd April 2016) - Kiel, Ewald; Heimlich, Ulrich; Markowetz, Reinhard; Braun, Annika; Weiß, Sabine
Abstract: The goal of the present study is to identify prospective special education teachers (SETs) who may have difficulties in coping with occupational stresses and burdens. International comparative studies show that SETs have a higher level of stress than their colleagues who work in the general school system. Compared with teachers in regular schools, SETs leave their profession at a higher rate. For this reason, the study focuses on so-called dysfunctional cognitions, which might increase stress in strenuous occupational situations and which have long-term harmful effects on health. The construct of dysfunctional cognitions is supposed to be a basis for developing supportive measures for teacher students with low stress tolerance. In the framework of the present study located in the German educational system, teacher students ( N = 333) from the special needs areas, including learning disability, mental disability, emotional/social disorders and sensory disabilities (hearing impairment, or speech or language disorders), are taken into account. A hierarchical cluster analysis and a discriminant analysis were used to identify four different clusters: Cluster 1 shows the lowest attitude level of equally all dysfunctional cognitions. Clusters 2 and 3 are characterised by higher degrees, especially of 'dependency', 'internalisation of failure' and 'personal standards (perfectionism)'. The fourth profile indicates the highest degree of the dysfunctional cognitions. Lower levels of dysfunctional cognitions (with the exception of perfectionism) occur together with a higher expectation of self-efficacy. No cluster applies for all teacher students of one specific special needs area. Prospective teachers in the area of mental disability are overrepresented in cluster 3, with a high level of internalisation of failure and dependency. Teacher students in the area of emotional/social disorders belong, to a considerable degree, to the 'risk' cluster. The profiles are used to develop measures for those teacher students who may experience difficulties in stressful occupational situations. Therefore, these student teachers need to be closely supported through additional intensive training elements and balanced career counselling.